Dengue control in the context of climate change: Views from health professionals in different geographic regions of China - Michael X. Tong; Alana Hansen; Scott Hanson-Easey; Jianjun Xiang; Scott Cameron; Qiyong Liu; Xiaobo Liu; Yehuan Sun; Philip Weinstein; Gil-Soo Han; Craig Williams; Afzal Mahmood; et al. (Elsevier, 2019)
Background: Dengue is a significant climate-sensitive disease. Public health professionals play an important role in prevention and control of the disease. This study aimed to explore dengue control and prevention in the context of climate change in China. Methods: A cross-sectional survey was conducted among 630 public health professionals in 2015. Descriptive analysis and logistic regression were performed. Results: More than 80% of participants from southwest and central China believed climate change would affect dengue. However, participants from northeast China were less likely to believe so (65%). Sixty-nine percent of participants in Yunnan perceived that dengue had emerged/re-emerged in recent years, compared with 40.6% in Henan and 23.8% in Liaoning. Less than 60% of participants thought current prevention and control programs had been effective. Participants believed mosquitoes in high abundance, imported cases and climate change were main risk factors for dengue in China. Conclusion: There were varying views of dengue in China. Professionals in areas susceptible to dengue were more likely to be concerned about climate change and dengue. Current prevention and control strategies need to be improved. Providing more information for staff in lower levels of Centers for Disease Control and Prevention may help in containing a possible increase of dengue. Keywords: Climate change, Dengue control, Infectious disease, Public health professional, China